2015
DOI: 10.1159/000368770
|View full text |Cite
|
Sign up to set email alerts
|

Development of Cerebral Gray and White Matter Injury and Cerebral Inflammation over Time after Inflammatory Perinatal Asphyxia

Abstract: Antenatal inflammation is associated with increased severity of hypoxic-ischemic (HI) encephalopathy and adverse outcome in human neonates and experimental rodents. We investigated the effect of lipopolysaccharide (LPS) on the timing of HI-induced cerebral tissue loss and gray matter injury, white matter injury and integrity, and the cerebral inflammatory response. On postnatal day 9, mice underwent HI by unilateral carotid artery occlusion followed by systemic hypoxia which resulted in early neuronal damage (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 85 publications
(106 reference statements)
1
22
0
1
Order By: Relevance
“…Second, the increase of oligodendrocyte lineage cells, as seen following 42d of UP exposure might indicate replenishment of oligodendrocytes upon initial loss in the acute phase following UP exposure [35]. Importantly, UP was administered at 80d of gestation which is the premyelinating stage of brain development with abundant vulnerable immature pre-oligodendrocytes, sensitive to glutamate receptor induced injury [36].…”
Section: Discussionmentioning
confidence: 99%
“…Second, the increase of oligodendrocyte lineage cells, as seen following 42d of UP exposure might indicate replenishment of oligodendrocytes upon initial loss in the acute phase following UP exposure [35]. Importantly, UP was administered at 80d of gestation which is the premyelinating stage of brain development with abundant vulnerable immature pre-oligodendrocytes, sensitive to glutamate receptor induced injury [36].…”
Section: Discussionmentioning
confidence: 99%
“…Rodent studies have shown that lesion size does no longer increase after 4 days after a neonatal hypoxic-ischaemic event. 21 Therefore the time window for neuroprotective strategies, that is prevention of cell death and inflammation, lies before 4 days after the insult. However, MSC transplantation at day 10 after hypoxia-ischaemia is still able to reduce brain damage.…”
Section: Mechanisms Of Action Of Mscsmentioning
confidence: 99%
“…In addition, myelination deficits, alterations in glial cells and reduced axonal density [37,38,39] have been found. In the work of Van de Berg et al [36], the atrophy in the mPFC was reported as a tendency.…”
Section: Discussionmentioning
confidence: 99%